Cooperative Learning Promoting Cultural Diversity and Individual Accountability: A Systematic Review - Tong Zhou; Jordi Colomer (MDPI AG, 2024)
Cooperative learning in physical education not only promotes the overall development of students, but also lays the foundation for lifelong learning and sustainable development from the perspectives of cultural integration and social responsibility. This study examined students' physical, social, emotional, and cognitive outcomes on the one hand. On the other hand, it focuses on the potential of cooperative learning to promote cultural diversity and personal responsibility. A systematic literature review of 50 articles selected according to the PRISMA guidelines revealed that the focus of CL applications varied according to the age of the students and multicultural contexts. At the micro level, physical and social domains were emphasized, while cognitive domains received less attention. CL was found to benefit motor skills (coordination, flexibility, strength) in students of different ages, to reduce negative emotions while promoting social skills and teamwork, and to improve cognitive skills and memory in junior students. At the macro level, CL can help students to improve self-reflection, reduce negative behaviors, and increase personal responsibility and cultural integration. The focus of researchers from different countries reflects educational philosophies and cultural differences, increasing the flexibility and universality of CL.